ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KETIMPANGAN PEREKONOMIAN DI JAWA TIMUR - Savitri, Diona; Ashar, Khusnul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Economic inequality in East Java Province is always above the national inequality every year. This is driven by the concentration of economic growth (growth pole) in urban areas that have greater economic activity. East Java Province excels in the industrial sector, this can be seen in the GRDP where Industry has the first position investment then in the second position the Transportation, Warehousing, and Communication sector. This is interesting because the transportation sector should be means to facilitate the mobilization of all sectors in East Java. However, the outcome of the relationship between the transportation sector and economic inequality-accessibility between regions has not been widely studied. The existence of socio-economic, endownment, government policies differences in each region have impacts on differences in welfare levels between regions. This type of research is quantitative. This study aims to test and analyze what factors affect economic inequality in East Java Province. This study uses secondary data, this study has a sample of 11 districts and 3 cities located in East Java Province. This study uses the Common Effect Model (CEM) test as the selected research model. The results of this study are the independent variable X (economic growth, Road Length, Road Stability, Ports, Passenger, Electrification Ratio, Labor, and Human Development Index) affect the dependent variable Y (inequality) simultaneously by 74,8% of the R-squared value.